Use of a Tourniquet in Total Knee Arthroplasty Causes a Paradoxical Increase in Total Blood Loss. (16th August 2017) - Schnettler, Timothy; Papillon, Natalie; Rees, Harold
Abstract : Background: A tourniquet in total knee arthroplasty has been used in an attempt to decrease perioperative blood loss; however, questions exist regarding safety and efficacy. Tranexamic acid has also been used to decrease blood loss by stabilizing clot formation. Because of these concerns, routine tourniquet use for total knee arthroplasty was discontinued by the senior author and routine tranexamic acid administration was commenced. The purpose of this study was to examine total perioperative blood loss with tourniquet use, with tourniquet use and routine use of tranexamic acid, and with tranexamic acid use alone without tourniquet. Methods: A retrospective cohort study of 132 patients in 3 groups was performed. The first group underwent total knee arthroplasty with limited tourniquet use only during cementing, the second group had the same protocol but with tranexamic acid administered, and the third group had tranexamic acid but no tourniquet used. Perioperative blood loss was calculated using the Gross formula. Results: The mean calculated blood loss was highest in the tourniquet-only group at 1, 591.39 mL (95% confidence interval [CI], 1, 064.97 to 2, 117.81 mL), decreased in the second group using tranexamic acid and tourniquet at 1, 215.34 mL (95% CI, 1, 104.93 to 1, 325.75 mL), and was lowest in the third group with tranexamic acid and no tourniquet at 1, 007.22 mL (95% CI, 878.78 to 1, 135.66 mL). Conclusions: Use of a limited tourniquet protocol during total knee arthroplasty resulted in a paradoxical increase in blood loss. Surgeons should consider omitting routine tourniquet use in total knee arthroplasty. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.